Cross Cultural Comparison of the Leadership Styles and Behaviour of Managers in the UK, USA and Southeast Asia - Roger Gill, (Asian Academy of Management Journal, 1998)
Cross Cultural Comparison of the Leadership Styles and Behaviour of Managers in the UK, USA and Southeast Asia(PDF not available)